CLINICAL EXPERIENCE WITH ETANERCEPT IN THE TREATMENT OF PATIENTS WITH ANKYLOSING SPONDYLITIS - O. A. Rumyantseva; A. G. Bochkova; M. M. Urumova; T. V. Dubinina; Sh. F. Erdes (Научно-практическая ревматология, 2018)
Etanercept (ETC), a soluble tumor necrosis factor-α (TNF-α) receptor, was registered for the treatment of spondyloarthritis in the Russian Federation in 2009. By now, results of prolonged treatment with this drug have been obtained in patients with ankylosing spondylitis (AS).Objective: to evaluate the efficiency and tolerability of long-term therapy with ETC in patients with AS.Subjects and methods. The follow-up included 60 patients with a documented diagnosis of AS (the 1984 New York criteria) and/or axial spondyloarthritis (the 2009 ASAS criteria), high activity (BASDAI >4), who received long-term (at least a year) regular therapy with subcutaneous ETC 50 mg weekly. Its effect was evaluated using the ASAS criteria.Results and discussion. ETC was the first TNF-α inhibitor used in 29 (48%) patients, including 22 (76%) patients who achieved partial remission; 7 (24%) patients who showed ASAS40 improvement. One patient was observed to have hepatotoxicity (alanine aminotransferase elevation to 72 U/l), therefore the drug was discontinued. 31 (52%) patients were switched to ETC after infliximab (n=24) or adalimumab (n=7) due to their poor tolerance and/or loss of effect. At the same time, ETC became the second anti-TNF-α drug in 21 (35%) patients and the third one in 10 (17%). During the therapy, 21 (68%) patients switched to ETC were noted to have ASAS40 improvement; 9 (29%) patients had partial remission. The insufficient effect of the drug was observed only in one patient (3%), in whom ETC was the third TNF-α inhibitor. The tolerability of ETC was generally satisfactory after switching from anti-TNF-α monoclonal antibodies (mAbs). Three patients developed de novo psoriasis that required therapy discontinuation in one patient; another male patient developed uveitis for the first time. In one female patient with AS associated with Crohn’s disease with loss of mAb effect, ETC became the third anti-TNF-α drug, during therapy with which there was no exacerbation of Crohn’s disease. The drug was well tolerated and highly effective in 8 patients, in whom ETC treatment was initiated at the age of 60 years and older: 6 (75%) achieved partial remission, 2 (25%) had ASAS40 improvement. Nine patients with previous and/or latent tuberculosis had no exacerbation of this disease during ETC therapy.Conclusion. During regular therapy with ETC, more than half of patients (52%) achieved partial remission according to the ASAS criteria, while this was more frequently achieved when the drug was used for the first time (76%) than when mAbs were switched to ETC (29%). Discontinuation of the latter due to adverse events was required only in 2 (3%) patients.